The full length of gene (x14K) that differentially expressed with retinoic acid (RA) treated Xenopus laevis embryos - K.Youssef , Abdelgader (Scientific Journal of University of Benghazi, 2026)
The differential display RT-PCR technique has allowed me to isolate a gene whose expression is upregulated by retinoic acid in stage 14 x.laevis embryos. The M-band pattern which are generated from this strategy ( probe paper), was appeared to be induced by retinoic acid. This M-CDNA fragment was used as a probe. The full length cDNA clone encoding region of this probe-fragment, termed x14K-gene was isolated from a kidney xenopus cDNA library. Sequencing of x14K-gene generated a continuous sequence of 2271 bp that contained an open reading frame of 1284 bp. Expression of x14K-gene in rabbit reticulocyte lysate produced a protein of the predicted size (47 kD) as determined from the largest open reading frame. A search of the GenBank database has identified that x14K-gene is more closely related to a Xenopus mitotic phosphoprotein MP43 than any other previously identified proteins. The two Xenopus proteins share 84% identity. Most lamins (lamin B1, A, C & C2) which were observed to be substrates of a family of cyclin-dependent kinases (CDKs), apppeared to have homology to the carboxy end of x14K-gene.